Historical Amnesia at Work: Reflecting about the "Absence in the Presence" of Female Authors in Saharan Arabic Manuscript Collections - Frede, Britta (Hawwa, 2025)
Saharan historians have often argued that women were integral to the local Islamic scholarly culture. These women frequently took on crucial roles such as teaching, writing, counselling, spiritual guidance and legal orientation. However, only very few historical sources document these activities. Starting from a list of authors, the analysis focuses on cultural remembering techniques that help preserve local intellectual achievements and illustrates how women were systematically excluded from local documentation of erudition. The author argues that due to established gendered practices within the traditional local Islamic scholarly culture, texts written by women were most likely to be at risk of disappearing. This is a classic example of historical amnesia at work. Nonetheless, approved details about women’s presence in Islamic intellectual life led to the conclusion that in the Saharan intellectual tradition, there is an “absence in the presence” of female Islamic scholarship.